2019
DOI: 10.2478/jengeo-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pattern and Extent of Deforestation in Akure Forest Reserve, Ondo State, Nigeria

Abstract: Forest Reserves in Southwestern Nigeria have been threatened by urbanization and anthropogenic activities and the rate of deforestation is not known. This study examined the vegetation characteristics of Akure Forest Reserve using optical remote sensing data. It also assessed the changing pattern in the forest reserve between 1986 and 2017. Global Navigation Satellite System (GNSS) receiver was used to capture the location of the prominent settlements that surrounded the Forest Reserve in order to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
3
5
0
1
Order By: Relevance
“…However, there has been a high precedence of farming within the forest reserve lands evident by the majority (70.8%) of the respondents having it as their major source of livelihoods. This level of agricultural activities confirms the aerial cover study of the reserve (Gbiri and Adeoye, 2019), which reported a 5.2%-increase in farmland, hence, constituting a major deforestation driver in the reserve. In addition, this finding corroborates that of (Appiah et al, 2009) in Ghana, who reported that farming for livelihood remains the largest deforestation factor in the country.…”
Section: Socio-economic Characteristics Of the Respondentssupporting
confidence: 87%
See 2 more Smart Citations
“…However, there has been a high precedence of farming within the forest reserve lands evident by the majority (70.8%) of the respondents having it as their major source of livelihoods. This level of agricultural activities confirms the aerial cover study of the reserve (Gbiri and Adeoye, 2019), which reported a 5.2%-increase in farmland, hence, constituting a major deforestation driver in the reserve. In addition, this finding corroborates that of (Appiah et al, 2009) in Ghana, who reported that farming for livelihood remains the largest deforestation factor in the country.…”
Section: Socio-economic Characteristics Of the Respondentssupporting
confidence: 87%
“…This high level of dependence on forest resources observed in the study communities is traceable to their high poverty level, as indicated by the poverty line, with an average household size of 7 earning approximately N430,000 naira annually. This further gives credence to the assertion by (Chao, 2012) that people who live adjacent to forest lands depend largely on the forests for their subsistence, and this could have consequently resulted to the deforestation and forest degradation in the Akure forest reserve which was reported by (Gbiri and Adeoye, 2019). The variation in the dependence and use of forest resources, as shown in Table 5, also found a base in the report of (Stephenson, 2011) that many people around the world depend on forests, not just for food but also for fuel, income, livestock grazing on forest lands, and collection of medicinal plants, all in varying degrees.…”
Section: Socio-economic Characteristics Of the Respondentssupporting
confidence: 73%
See 1 more Smart Citation
“…З появою нового джерела інформації, супутникових даних, у світі виникло багато нагальних питань і проблем, які вирішуються за допомогою саме цих даних. Зокрема, це завдання моніторингу сільськогосподарських площ [1], лісового покриву [2], водних об'єктів [3] тощо. У вирішенні цих питань зацікавлена передусім держава та уряд країни, в якій проводиться дослідження.…”
Section: вступunclassified
“…The Nigerian Forestry Information System (NFIS) developed by the Forestry Association of Nigeria for the Federal Department of Forestry with the financial support provided by the Food and Agriculture Organization of the United Nations (FAO), which was supposed to contain relevant spatial information from the forestry sub-sector was completely devoid of data from the 36 States of the Country. However, previous notable researches like [15], [9], [13], [14], [12], [4], [3], and [7] among others based their studies on deforestation, land use and land cover changes, and forest management in Nigerian forest reserves. None of these studies contributed their research outcome to the Nigerian Forestry Information System (NFIS).…”
Section: Introductionmentioning
confidence: 99%